Epistemological findings in management research applying immanient critique, from humanism to the humanistic curriculum (GEON Journal (Management, Organizations and Business), 2022)
Problem: The epistemological perspectives in management research, as well as in any discipline, must be constantly reviewed to identify opportunities for theoretical advancement. Most management schools in Latin-America subscribe to the humanistic management epistemology, yet operations management, being a part management curricula, identifies with positivism. The starting point of this article is the tension between the two epistemologies in management. Objective: to confront the two seemingly antagonistic epistemological perspectives in management research, coexistent in the humanist management curriculum. Reflecting from the humanistic first principles, to propose new epistemological perspectives. Materials and methods: The article uses textual exegesis for data collection, and Hegelian dialectics applying the method of immanent critique, building on, theses-antithesis- synthesis for data analisys. Results: The article finds possible epistemological perspectives for management research, and presents them in the ontological, epistemological, and methodological levels. It finds research opportunities regarding ontology, in process studies, and systems theory. Regarding epistemology, it finds opportunities in the study of history, multidisciplinary studies, territoriality, and cybernetics. Methodologically it unveils opportunities for research in the application of the methods of philosophy, and panexperientialism. Discussion: The study discusses the meaning of humanities in management studies. Conclusions: The need to explore new philosophical positions in management research from the initial definitions. Contribution/originality: This study discusses one of the relevant epistemological perspectives in Latin-American management.
Keywords: administration; epistemology; humanism; management; ontology; process; M19 Business Administration; B15 History of Economic Thought through 1925: Historical; Institutional; Evolutionary; B25 History of Economic Thought since 1925: Historical; Institutional; Evolutionary; Austrian; Stockholm School